Preparation and characterization of crystalline nanocellulose from keya (Pandanus tectorius) L. fiber as potential reinforcement in sustainable bionanocomposite: A waste to wealth scheme - Md. Ismail Hossain; Md. Mahmudur Rahman; Bijoy Chandra Ghos; Md. Abdul Gafur; Md. Ashraful Alam; M. Ahasanur Rabbi (Carbohydrate Polymer Technologies and Applications)
Nowadays naturally available bio-renewable plant fiber-derived crystalline nanocellulose(CNC) is very attractive to researchers due to its outstanding physicochemical, thermomechanical, morphological properties and eco-friendly nature. Here, CNC was produced from a very much new, innovative, and beneficial source namely Keya leaf fiber (agro-waste biomass). Keya leaves were chosen due to their extensive abundance in Bangladesh which is useless and even not considered as cattle food. The extracted CNC was characterized by FTIR-ATR,TGA/DTG/DTA, FESEM,EDX,XRD,DLS,UV-vis-NIR, and zeta potential analysis. Morphological changes of the subjected samples have been investigated by FESEM and the surface elemental change by EDX analysis. The elimination of impurities and other components from the fiber in each step has been evaluated by monitoring the introduction of new peaks and perishing existing peaks in FTIR patterns. Significant changes have been noticed in the intensities and peak pattern of the XRD analysis and the crystallinity index was promoted gradually from RF(45.35 %) to CNC(61.31 %). The thermal analysis showed that the maximum rate of decomposition(μg/min) decreases with the chemical modification in order of RF(1440) > ATF(3510) > BF(3280) > CNC(600). Due to these outstanding findings, the newly produced CNC can be beneficially used as a reinforcement to produce multifunctional bionanocomposites that should have a good agreement with sustainable environmental protection.